FORENSIC INVESTIGATION OF THE INVESTIGATION OF CRIMES OF INTERNATIONAL CHARACTER - Калюжний, Р. А. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
This work of the amendment can be attributed to the scientific works, in which under the current conditions of reforming criminal proceedings at the monographic level considered theoretical and applied problems criminalistic support for the investigation of crimes of an international nature